A study of relative dissociation energy through electro-optics effect as a potential tool for evaluation of cooking oil quality. Issue 1 (July 2021) - Septiani, A; Utomo, G N; Sumariyah; Richardina, V; Sugito, H; Azam, M; Soesanto, Q M B; Firdausi, K S
Abstract: The electro-optics effect is a potential tool to observe and evaluate different oil quality. In this research, we study relative dissociation energy through the electro-optics effect to evaluate vegetable oil quality. Some vegetable cooking oil samples with different quality were placed in an external potential difference between parallel plates to obtain the electro-optical characteristics by measuring the polarization change using red pointer laser (650 nm). The empirical values of dissociation energy was obtained by fitting experimental data of the average polarization changes per unit potential difference with Lenard-Jones potential formula under the assumption that the interaction between molecules is a Vander Waals interaction. The results show that the average change in polarization is proportional to Lenard-Jones potential energy. An important result showed that a good oil quality is indicated by relatively high dissociation energy. Reducing the oil quality leads to increasing relative dissociation energy. This provides electro-optics as a very potential method in differentiating various cooking oil qualities and new perspective of interacting linear polarized light with oil molecules.